Long Short Term Memory For Comparison Between Bank Syariah Indonesia And PT Bank Artos Indonesia Shares - Rizqiana, Zulfanita Dien; Akhsan, Izzat Muhammad; Priyanto, Intan Indrasara; Maharani, Aninda Sabila (Universitas Trilogi, 2024)
The growth of the capital market in Indonesia has increased from year to year. Based on data from the Indonesia Central Securities Corporation (KSEI), there has been an increase in investor growth in the capital market by 2.34%, mutual funds by 2.44%, and shares by 1.34% until August 2024. The demographic of individual investors in the capital market is dominated by Generation Z who are younger than from 30 years as much as 55.07% in August 2024 (KSEI, 2024). Shares are a form of investment that has the potential for large profits but with small risks. One sector that Gen Z is interested in investing in is the financial sector. The aim of this research is to compare the share prices of Bank Syariah Indonesia and Bank PT Ban Artos Indonesia Tbk using a Neural Network with the Long Short Term Memory (LTSM) algorithm. The data used in this research is secondary data on BSI and PT Bank Artos Indonesia Tbk share prices taken from the investing.com website. The data period used is from 01 September 2021 – 01 September 2024. Based on the results of stock price forecasting using a Neural Network with the LTSM algorithm, RMSE value for both models is for BSI 75.0757 and 91.795 for PT. Bank Artos Indonesia Tbk. A comparison of the predicted share prices of PT Bank Arto Indonesia Tbk and BSI shows that BSI's share price performance is superior to that of PT Bank Arto Indonesia Tbk.